LEMBAGA BANTUAN HUKUM DALAM PERSPEKTIF HAK ASASI MANUSIA - Agustina, Enny; Eryani, Susanti; Dewi, Virna; Pawari, Rahmiati Ranti (Solusi, 2021)
One form of protection of human rights is providing legal assistance. This research discusses the role and position of legal aid institutions from a human rights perspective as well as the role of the state in empowering legal aid institutions as a means of legal protection in society. This study uses a normative research method, in which the data sources used come from literature books, law magazines, legal journals, and other library materials. The conclusion of this research is that legal aid is the most human right of every person and is guaranteed by the laws of Indonesia. In fact, legal aid activities are currently running in accordance with the expectations of the community, as outlined by the provisions of the prevailing laws and regulations. Its functions and roles as law enforcement officers in the field of counseling and information as well as legal reform, until now have been very helpful and seen in the practice of constitutional law in Indonesia. The provision of legal aid as a state obligation to fulfill the constitutional rights of citizens is expanded in Law Number 16 of 2011 concerning Legal Aid by involving not only advocates, but also paralegals, lecturers and law faculty students.